2018
DOI: 10.1016/j.ejmech.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

MMB triazole analogs are potent NF-κB inhibitors and anti-cancer agents against both hematological and solid tumor cells

Abstract: Triazole derivatives of melampomagnolide B (MMB) have been synthesized via click chemistry methodologies and screened against a panel of 60 human cancer cell lines. Several derivatives showed promising anti-cancer activity, affording growth inhibition (GI) values in the nanomolar range (GI = 0.02-0.99 μM). Lead compound 7h exhibited EC values of 400 nM and 700 nM, respectively, against two AML clinical specimens. Compound 7h was significantly more potent than parthenolide as an inhibitor of p65 phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…The structures of SARS-CoV-2 proteins used in this study were retrieved from I-TASSER (neural networkbased structure predictions) [9]. Proteins were preprocessed using the Protein Preparation Wizard module of Schrödinger's Prime module by the MMGBSA method, using molecular mechanics, the generalized Born solvent model, and solvent accessibility [18][19][20].…”
Section: Structure-based Targeted Dockingmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures of SARS-CoV-2 proteins used in this study were retrieved from I-TASSER (neural networkbased structure predictions) [9]. Proteins were preprocessed using the Protein Preparation Wizard module of Schrödinger's Prime module by the MMGBSA method, using molecular mechanics, the generalized Born solvent model, and solvent accessibility [18][19][20].…”
Section: Structure-based Targeted Dockingmentioning
confidence: 99%
“…Unbiased or whole-protein docking was conducted using AutoDock-Vina molecular docking package [18,23,24]. Briefly, proteins and drugs were prepared in Vina format prior to docking.…”
Section: Unbiased Protein-ligand Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…3), was effective and potent against several cancer cell lines including leukaemia (GI 50 = 0.10-0.23 µM), colon (GI 50 = 0.14-1.17 µM), melanoma (GI 50 = 0.15-1.47 µM), renal (GI 50 = 0.02-0.70 µM), ovarian (GI 50 = 0.15-1.86 µM), prostate (GI 50 = 0.72-0.83 µM), and breast (GI 50 = 0.17-1.03 µM) cancer cell line subpanels. 46 Further investigation indicated that triazole compound 2 was a potent inhibitor of nuclear factor (NF)-kB and cell proliferation in TMD-231 (MDA-MB-231) cell line. Moreover, treatment of TMD-231 cells with derivative 2 decreased the DNA binding activity of NF-kB by inhibiting p65 phosphorylation mediated by inhibitor of NF-kB kinase (IKK)-b and increasing basal IkBα levels via inhibition of substantial NF-kB activation and IkBα turnover.…”
Section: Introductionmentioning
confidence: 99%
“…The system was next equilibrated using the NPT protocol (constant number of particles, pressure and temperature) with default temperature (300 o K) and pressure (1 bar). MD simulations were then conducted for 100-200 ns using Desmond's GPU-based simulation method [18][19][20][21][22]. Results were analyzed using the Simulation Interactions Diagram module from Schrödinger Maestro.…”
Section: Molecular-dynamic Simulation Of Protein-drug Complexesmentioning
confidence: 99%